Foo, a Japanese-American prisoner of the Rising Sun : the secret prison diary of Frank "Foo" Fujita - Fujita, Frank, 1921- (War and the Southwest series, 1993)
During his time as a POW, Frank "Foo" Fujita kept a diary of daily happenings, embellished with drawings of life in the camp. He secreted the diary in the walls of his barracks, as the practice was forbidden. That diary forms the basis of these memoirs. Fujita's memoirs are also unique in that he was one of the fewer than nine hundred Americans taken prisoner on the island of Java. The bulk of American POWs in Japanese hands surrendered in the Philippines, and most of the published POW memoirs reflect their experience. Fujita's account of the defense of Java and of the fate of the "Lost Battalion" of Texas artillerymen serves to distinguish this memoir from others. At one point while a POW in Japan, Fujita was forced to be part of the Japanese radio group broadcasting propaganda. After the war, he testified at some of the war crime trials in San Francisco, and the diary on which this book is based was used as evidence in those trials.